Telemonitoring-Based Cardiac Care to Reduce Readmissions in Coronary Heart Disease Patients - Hariyono Hariyono; Sri Pantja Madyawati; Leo Yosdimyati Romli; Chin Xuan Tan; Shifa Fauziyah; Teguh Hari Sucipto (Jurnal Kesehatan Masyarakat, 2025)
Coronary heart disease (CHD) continues to be a leading cause of hospital readmissions, especially among elderly individuals with low educational attainment and limited understanding of health information. This research aimed to evaluate how cardiac care management influences the frequency of hospital readmission in patients diagnosed with CHD. Employing a quasi-experimental method with a one-group pretest-posttest design, the study involved 100 participants at Jombang Hospital, chosen through purposive sampling. Information regarding readmission rates was gathered before and after the intervention using structured questionnaires and assessed through the Wilcoxon signed-rank test. Before receiving the intervention, 25% of patients had been readmitted more than twice, while none avoided readmission altogether. Following the management program, only 5% experienced multiple readmissions, and 25% reported none. The statistical outcome demonstrated a significant difference (p = 0.002), proving that cardiac care interventions consisting of educational support, family involvement, and consistent follow-up effectively decreased patient readmission. Most participants were aged between 61 and 75, male, and had only completed elementary school, all of which are factors associated with poor disease self-management. This trial confirms that integrated cardiac care management greatly improves the outcomes of recovery and decreases the risk of rehospitalization in CHD patients.